Hydrothermal stability improvement of NiPt-containing γ-Al2O3 catalysts tested in aqueous phase reforming of glycerol/water mixture for H2 production. (14th September 2017) - El Doukkali, M.; Iriondo, A.; Miletic, N.; Cambra, J.F.; Arias, P.L.
Abstract: The hydrothermal stability of Ni and NiPt-containing γ-Al2 O3 catalysts in aqueous phase reforming (APR) of glycerol/water mixture (C3 H8 O3 /H2 O, 10% w/w) was investigated putting in evidence the influence of the preparation method; sol–gel in basic medium (SGB) and impregnation on an in-house prepared sol–gel γ-Al2 O3 support (SGI). All developed catalysts were characterized by ICP-AES, TPR-H2, in-situ heating XRD-O2, DSC/TG-N2 /O2 and ex-situ reduction of XRD-H2, N2 physisoption and TEM techniques. The results indicate that SGI method and calcination treatment at 750 °C were crucial in extending the catalytic useful life of NiPt-containing γ-Al2 O3 catalysts, resulting in an adequate distribution of NiPt metallic particles and good stability of γ-Al2 O3 support against the severe hydrothermal conditions of APR process. The SGI method led to form stable NiPt catalysts with relatively big Ni particles and stable hydrothermal properties of γ-Al2 O3 support, while the SGB catalysts exhibited well-dispersed Ni particles but unstable catalytic behavior. These last catalysts presented high glycerol conversions during the first hours of APR glycerol/water reaction, however, an important decrease in terms of glycerol conversion was observed after 24 h time-on-stream. The experimental results suggested that the most suitable stable and active catalyst was the NiPt/ASGI7 (better than >NiPt/ASGI6 > NiPt/ASGI5 >>> NiPt/ASGB7). This catalyst showed best catalytic activity and good catalytic stability along 56 h of time-on-stream, reaching, at steady state, highest total glycerol conversion (≈79%) and glycerol into gaseous products (≈57%) in APR reaction of glycerol/water mixture for hydrogen generation. Highlights: The hydrothermal stability of Ni/NiPt-containing γ-Al2 O3 catalysts in glycerol APR was studied. SGI method and calcination at higher T were crucial to develop well-stable NiPt/γ-Al2 O3 catalyst. SGI method form bigger Ni particles/stable γ-Al2 O3, while SGB exhibited well-dispersed particles. SGI catalysts are more stable in glycerol APR process but SGB catalysts shown to be more active. The most suitable activity/stability behavior in glycerol APR was obtained by NiPt/ASGI7 catalyst.